The Influence of Electronic Word of Mouth and Price Sensitivity on Sustainable Food Consumption Intentions: Environmental Concern Mediation - Deswita, Yohana Fica Silvia; Rahmawati, Christina Heti Tri; Kristia (School of Business, IPB University (SB-IPB), 2024)
Background: Sustainable consumption habits by purchasing and consuming environmentally friendly products are changes made to maintain natural resources and prevent non-environmental practices carried out by producers. Purpose: The research objectives are to determine (1) the influence of electronic Word of Mouth (e-WOM), price sensitivity, and environmental concern on sustainable food consumption intentions, (2) environmental concern mediates the influence of e-WOM on sustainable food consumption intentions, and (3) environmental concern mediates the influence price sensitivity to sustainable food consumption intentions. Design/methodology/approach: This research uses a population of all followers from Instagram social media accounts at the green restaurants Nanamia Pizzeria and Warung Bumi Langit. The respondents of this research were 200 people, dominated by Generation Z using a purposive sampling technique. The data analysis technique is Partial Least Square with SmartPLS 3.29 software. Findings/Result: The research results show (1) e-WOM, price sensitivity, and environmental concern influence sustainable food consumption intentions, (2) environmental concern partially mediates the influence of e-WOM on sustainable food consumption intentions, and (3) environmental concern partially mediates the influence of price sensitivity on consumption intentions sustainable food. This model explains 56.4% of sustainable food consumption variation through e-WOM variables, price sensitivity, and environmental concerns. Conclusion: This finding highlights the crucial role of environmental concern in shaping sustainable food consumption intentions and is especially important for sustainable food restaurants like Nanamia Pizzeria and Warung Bumi Langit. To attract more customers, these restaurants should focus on marketing strategies that highlight the environmental impact of their products while also implementing sustainable principles in their operations, including using sustainable resources, waste management, and supporting local farmers.Originality/value (State of the art): This research contributes to the limited discourse in marketing literature by uniquely integrating e-WOM and price sensitivity with environmental concerns affecting sustainable food consumption, specifically in the context of green restaurants in Indonesia. Keywords: e-WOM, environmental concern, sustainable food consumption intentions, price sensitivity